Donor-receptor type polymer-based flexible thermoelectric thin film and preparation method thereof

The donor-acceptor type polymer-based flexible thermoelectric film prepared by mixing single-wall carbon nanotubes with PffBT4T-2OD is solved, and the problems of high thermal conductivity and high brittleness of inorganic thermoelectric materials are achieved, achieving high performance and low Cost preparation of thermoelectric materials.

CN119486570APending Publication Date: 2025-02-18JIANGSU HENGLIU TECHNOLOGY CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411036287.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-07-31
Publication Date
2025-02-18

AI Technical Summary

Technical Problem

Inorganic thermoelectric materials have high thermal conductivity, the methods to reduce thermal conductivity are costly and raw materials are scarce, so they are not suitable for mass production. At the same time, inorganic materials are highly brittle and difficult to adapt to complex working environments.

Method used

The donor-acceptor type polymer-based flexible thermoelectric film was prepared by ultrasonic dispersion, magnetic stirring and vacuum filtration using a donor-acceptor type polymer-based flexible thermoelectric film formed by mixing single-wall carbon nanotubes and PffBT4T-2OD.

Benefits of technology

The prepared flexible thermoelectric film has high conductivity and high Seebeck coefficient, excellent thermoelectric performance, suitable for thermoelectric materials, and is highly flexible and low in cost, suitable for industrial production.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119486570A_ABST
    Figure CN119486570A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of thermoelectric materials, and discloses a donor-acceptor type polymer-based flexible thermoelectric film and a preparation method thereof, and the flexible thermoelectric film is formed by mixing and doping single-walled carbon nanotubes, has a structure containing benzothiadiazole (BTH), and has very excellent hot spot performance. The specific preparation method comprises the following steps: respectively dissolving the single-walled carbon nanotube and PffBT4T-2OD in chlorobenzene and trichloromethane through ultrasonic oscillation, mixing, stirring and oscillating to disperse the mixture in the solution, preserving the mixture on filter paper through vacuum filtration, and finally drying the mixture on the filter paper in vacuum to obtain the composite film. The method provided by the invention is simple and convenient, easy to implement and suitable for industrial production, and the prepared film has the characteristics of high conductivity and high Seebeck coefficient, has the characteristics of good toughness, difficulty in damage and small environmental pollution compared with an inorganic thermoelectric material, and is an excellent organic thermoelectric composite film.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of thermoelectric materials, in particular to a donor-acceptor type polymer-based flexible thermoelectric film and a preparation method thereof. Background Art

[0002] Thermoelectric materials are materials that use the movement of carriers inside solids to achieve mutual conversion between thermal energy and electrical energy. The performance of thermoelectric materials is characterized by the thermoelectric figure of merit ZT, ZT = S 2 σT / κ, where S represents the Seebeck coefficient, σ represents electrical conductivity, and κ represents thermal conductivity. Therefore, excellent thermoelectric performance is mainly manifested in high Seebeck coefficient, high electrical conductivity, and low thermal conductivity. In the early stage of the development of thermoelectric materials, research on inorganic thermoelectric materials with antimony, bismuth, and tellurium as the main elements has achieved certain results, but inorganic thermoelectric materials have the following disadvantages: (1) The thermal conductivity is high, and the method of reducing thermal conductivity is too expensive. The raw materials are scarce and the cost is high, which is not suitable for mass production; (2) Some metal materials are toxic, and excessive use will increase the environmental burden and endanger human health; (3) Inorganic materials are brittle and cannot adapt to various complex working environments like flexible materials.

[0003] In order to solve the problems caused by inorganic thermoelectric materials, people have turned their attention to organic materials. People have found that the thermoelectric materials formed by combining single-walled carbon nanotubes with organic polymers have the characteristics of high electrical conductivity, low thermal conductivity, and high Seebeck coefficient. In addition, organic thermoelectric materials have the characteristics of high toughness, not easy to damage, and light weight compared with inorganic thermoelectric materials. In addition, the process of combining single-walled carbon nanotubes with organic polymers is also very simple and suitable for industrial development.

[0004] In order to improve the predicament of current thermoelectric materials under the current environment, the purpose of the present invention is to prepare a flexible thermoelectric film, by dissolving single-walled carbon nanotubes and PffBT4T-2OD in chlorobenzene and chloroform respectively, mixing and stirring, then vacuum filtering, and then vacuum drying into a film. The film has high conductivity and Seebeck coefficient because of the large material planarity, which is conducive to carrier transport, and therefore has excellent thermoelectric performance and is suitable for thermoelectric materials. Summary of the invention

[0005] 1. Technical issues to be resolved

[0006] In view of the shortcomings of the prior art, the present invention provides a donor-acceptor type polymer-based flexible thermoelectric film and a preparation method thereof. The prepared film has high electrical conductivity and Seebeck coefficient, excellent thermoelectric performance, and is suitable for the advantages of thermoelectric materials. It solves the problem that inorganic thermoelectric materials have high thermal conductivity and methods for reducing thermal conductivity are too expensive, raw materials are scarce, costs are high, and are not suitable for mass production.

[0007] (II) Technical solution

[0008] To achieve the above objectives, the present invention provides the following technical solutions: a donor-acceptor type polymer-based flexible thermoelectric film and a preparation method thereof, wherein the flexible thermoelectric film is a composite material formed by mixed doping of single-walled carbon nanotubes and PffBT4T-2OD and having a BTH and thiophene structure.

[0009] Preferably, a method for preparing a flexible thermoelectric film comprises the following steps:

[0010] S1, PffBT4T-2OD and single-walled carbon nanotubes were dissolved in chloroform and chlorobenzene solvents respectively and then ultrasonically dispersed for 30 min to obtain PffBT4T-2OD solution and single-walled carbon nanotube solution;

[0011] S2, mixing the PffBT4T-2OD solution and the single-walled carbon nanotube solution, pouring the two solutions into a beaker, stirring magnetically for 30 minutes, and then ultrasonically dispersing for 30 minutes to fully mix the two solutions to form a mixture;

[0012] S3. The mixture solution is vacuum filtered with filter paper to remove the solvent in the mixture solution, and the mixed doped PffBT4T-2OD and single-walled carbon nanotubes are retained on the filter paper. Finally, the product on the filter paper is flattened and dried to obtain a flexible thermoelectric film.

[0013] Preferably, the PffBT4T-2OD is a PffBT4T-2OD having a donor-acceptor type (DA) conjugated polymer, and its structural formula is:

[0014]

[0015] Preferably, the carbon nanotubes are ultra-high purity single-walled carbon nanotubes with a purity of 95%.

[0016] Preferably, in step S2, the mass ratio of PffBT4T-2OD to single-walled carbon nanotubes in the mixture solution is 2:6.

[0017] Preferably, the specific operation method of step S3 is: using 0.45 μm microporous filter paper to filter the mixture solution by vacuum filtration, retaining the mixture in the mixture solution on the filter paper and removing the solvent, and then vacuum drying the mixture on the filter paper to obtain a flexible thermoelectric film.

[0018] Compared with the prior art, the present invention provides a donor-acceptor type polymer-based flexible thermoelectric film and a preparation method thereof, which has the following beneficial effects:

[0019] 1. The donor-acceptor type polymer-based flexible thermoelectric film and its preparation method, the invention provides a kind of application and preparation of flexible thermoelectric film, after PffBT4T-2OD and single-walled carbon nanotubes are dissolved in chloroform and chlorobenzene respectively by ultrasonic dispersion, then by stirring and mixing and ultrasonic dispersion, finally by filtering and drying to make flexible hot spot film. The film is owing to being able to allow PffBT4T-2OD to wrap up single-walled carbon nanotubes, so that its mixture has strong π-π conjugated effect, so that the film has high conductivity, the characteristics of high Seebeck coefficient. The preparation process step provided by the invention is simple and convenient and has better effect, which is very suitable for industrial production. The flexible thermoelectric film prepared is not only excellent in thermoelectric performance, but also flexible and high and not easy to damage, and the material cost is relatively low, and it is a kind of excellent composite thermoelectric material with excellent development prospects. BRIEF DESCRIPTION OF THE DRAWINGS

[0020] Figure 1 The structural formula (above) and reagent diagram (below) of PffBT4T-2OD, a donor-acceptor type (DA) conjugated polymer of the present invention;

[0021] Figure 2 The image of the donor-acceptor type (DA) conjugated polymer PffBT4T-2OD and ultra-high purity single-walled carbon nanotubes fully dispersed in chloroform and chlorobenzene (the left side is the ultra-high purity single-walled carbon nanotubes, and the right side is the donor-acceptor type (DA) conjugated polymer PffBT4T-2OD);

[0022] Figure 3 This is a physical picture of the composite thermoelectric film of Example 1 of the present invention;

[0023] Figure 4 A physical picture of the German Lindsay Seebeck coefficient / resistance tester LSR-2 used in the present invention;

[0024] Figure 5 The graph of the conductivity of the composite thermoelectric film with different PffBT4T-2OD-SWCNTS ratios of the present invention varies with temperature;

[0025] Figure 6 The graph of Seebeck coefficient of different PffBT4T-2OD-SWCNTS ratios of the present invention versus temperature;

[0026] Figure 7 The power factor of different PffBT4T-2OD-SWCNTS ratios of the present invention varies with temperature;

[0027] Figure 8 This is a field emission scanning electron microscope image of the composite thermoelectric thin film material of the present invention;

[0028] Fig. 9This is a Raman spectrum of the composite thermoelectric thin film material of the present invention;

[0029] Fig.10 This is an X-ray photoelectron spectroscopy surface analysis diagram of the composite thermoelectric thin film material of Example 2;

[0030] Fig.11 It is a schematic diagram of the preparation process of the flexible thermoelectric film of the present invention. DETAILED DESCRIPTION

[0031] The following will be combined with the drawings in the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0032] Embodiment 1:

[0033] Preparation of a flexible thermoelectric film with a ratio of PffBT4T-2OD and ultra-high purity single-walled carbon nanotube material of 2:6. In this embodiment, the PffBT4T-2OD used is a donor-acceptor type (DA) conjugated polymer of poly[(5,6-difluoro-2,1,3-benzothiadiazole-4,7-diyl)-alt-(3,3"'-di(2-octyldodecyl)-2,2'; 5',2"; 5",2"'-quaternary thiophene-5,5"'-diyl)] (abbreviated as PffBT4T-2OD), and its structural formula and reagent diagram are as shown in Figure 1 As shown, the purity of the ultra-high purity single-walled carbon nanotubes (SWCNTS) used is 95%, the purity of the chlorobenzene used is 99.5%, and the purity of the chloroform used is analytically pure. The specific preparation method includes the following steps:

[0034] (1) Place 2 mg of PffBT4T-2OD and 6 mg of SWCNTS into two test tubes with lids, and use a pipette to measure 15 mL of chloroform and 30 mL of chlorobenzene and add them to the test tubes of PffBT4T-2OD and SWCNTS respectively;

[0035] (2) Two test tubes were respectively tightened with lids, put into an ultrasonic cleaning machine and vibrated for 30 min simultaneously, so that PffBT4T-2OD and SWCNTS were completely dispersed in the solution, the power of the ultrasonic oscillator was 80 W, and the frequency was 40 KHz. After the ultrasonic oscillation, the solution in the two test tubes was poured into a beaker and a clean stirrer was added to the beaker, and then the beaker was placed in a magnetic stirrer and stirred for half an hour so that the two solutions were fully mixed to form a mixture, and then the mixed solution was put into an ultrasonic cleaning machine and vibrated for 30 min, and the mixture formed by the mixed doping of PffBT4T-2OD and single-walled carbon nanotubes in the dispersed solution.

[0036] (3) Take a 0.45 μm microporous filter paper, moisten it with ethanol, and make it closely adhere to the sand filter of the vacuum filter; turn on the vacuum filter, and when the pressure reaches -0.1 MPa, pour the dispersed solution in step (2) into the filter cup, remove the chlorobenzene filter sample and keep the mixed doped PffBT4T-2OD and single-walled carbon nanotubes on the filter paper; remove the filter paper, flatten it with weighing paper, and place the filter paper in two inverted glass dishes for compaction; place the filter paper and the glass dishes together in a vacuum drying oven, vacuum dry them at -0.1 MPa and 60°C for 24 h, peel off the film from the filter paper, and obtain a flexible thermoelectric film with a PffBT4T-2OD and SWCNTS ratio of 2:6 (the actual film is as shown in FIG. Figure 3 (shown)

[0037] Embodiment 2:

[0038] Preparation of a flexible thermoelectric film in which the ratio of PffBT4T-2OD to ultra-high purity single-walled carbon nanotube materials is 4:6. The preparation method is the same as that in Example 1, except that: in step (1), 4 mg PffBT4T-2OD and 6 mg SWCNTS are respectively placed in a test tube with a lid, and 40 mL of chloroform and 30 mL of chlorobenzene are measured with a pipette and added to the test tubes of PffBT4T-2OD and ultra-high purity single-walled carbon nanotubes, respectively; a flexible thermoelectric film in which the ratio of PffBT4T-2OD to ultra-high purity single-walled carbon nanotube materials is 4:6 is prepared.

[0039] Embodiment three:

[0040] Preparation of a flexible thermoelectric film in which the ratio of PffBT4T-2OD to ultra-high purity single-walled carbon nanotube materials is 6:6. The preparation method is the same as that in Example 1, except that: in step (1), 6 mg of PffBT4T-2OD and 6 mg of SWCNTS are respectively placed in a test tube with a lid, and 45 mL of chloroform and 30 mL of chlorobenzene are measured with a pipette and added to the test tubes of PffBT4T-2OD and ultra-high purity single-walled carbon nanotubes, respectively; a flexible thermoelectric film in which the ratio of PffBT4T-2OD to ultra-high purity single-walled carbon nanotube materials is 6:6 is prepared.

[0041] Example 4: Preparation of a flexible thermoelectric film in which the ratio of PffBT4T-2OD to ultra-high purity single-walled carbon nanotube materials is 8:6. The preparation method is the same as that in Example 1, except that: in step (1), 8 mg of PffBT4T-2OD and 6 mg of SWCNTS are respectively placed in a test tube with a lid, and 60 mL of chloroform and 30 mL of chlorobenzene are taken with a pipette and added to the test tubes of PffBT4T-2OD and ultra-high purity single-walled carbon nanotubes, respectively; a flexible thermoelectric film in which the ratio of PffBT4T-2OD to ultra-high purity single-walled carbon nanotube materials is 8:6 is prepared.

[0042] The thermoelectric performance of the composite thermoelectric films prepared in Example 1, Example 2, Example 3 and Example 4 was tested using a German Lindsay Seebeck coefficient / resistance tester LSR-2. Figure 4 , the test steps are as follows: open the cooling water circulation system, open the furnace body, open the computer software, remove the nickel box, open the thermocouple and platinum electrode base, fix the cut composite thermoelectric film (2.4cm×0.4cm) on the special film mold, and then clamp the film with the upper and lower platinum electrodes, and then gradually bring the thermocouple close to the film. After the two are fully in contact, click "test contact" on the test software, and it will display "contactOK", indicating that the sample installation is complete. Put on the nickel box, close the furnace body, turn on the vacuum pump, reduce the air pressure to -0.1Mpa, close the vacuum pump valve, open the helium valve, adjust the air pressure to 0Mpa, and repeat three times. Open the test software, fill in the parameters such as film thickness, temperature range, heating rate, etc., and after the tester is finished running, obtain the corresponding thermoelectric data. The curve of the conductivity of the composite thermoelectric film with different material ratios changes with temperature is shown in the following figure. Figure 5 As shown in Figure 1, when the material ratio is PffBT4T0-2OD:SWCNTS=2:6, the film conductivity is the highest, reaching 688S·cm-1; the curves of the Seebeck coefficient of the composite thermoelectric film with different material ratios as a function of temperature are shown in Figure 1. Figure 6 As shown in Figure 1, when the material ratio is PffBT4T0-2OD:SWCNTS=8:6, the Seebeck coefficient of the film is the highest, reaching 59μV·K-1; the power factor PF is the product of the conductivity and the square of the Seebeck coefficient. The power factor changes with temperature as shown in Figure 1. Figure 7 As shown in the figure, the conductivity of the material ratio of PffBT4T0-2OD:SWCNTS=2:6 is the highest, and the Seebeck coefficient is the lowest when the material ratio is PffBT4T0-2OD:SWCNTS=2:6. However, since the Seebeck coefficients of the various ratios are not much different, and the conductivity of the material ratio of 2:6 is very different from the others, the two performance data are combined, according to PF=S 2σ, it can be seen that the power factor of the thermoelectric film with PffBT4T-2OD:SWCNTS=2:6 is the highest, reaching 210μW·m-1K-2. Therefore, the thermoelectric performance of the composite film is the best.

[0043] At the same time, the thin films of Example 1, Example 2, Example 3, and Example 4 were analyzed using a field emission electron scanning microscope FESEM. The FESEM images are shown in FIG. Figure 8 As shown. The single-walled carbon nanotubes form an interwoven network with few and large holes, and some of them are agglomerated. After the polymer wraps the single-walled carbon nanotubes, the agglomeration phenomenon is significantly reduced, and the network structure is more obvious, making the curled single-walled carbon nanotubes more extended. This phenomenon becomes more obvious as the proportion increases. The composite film, polymer and single-walled carbon nanotubes of Example 1 are subjected to Raman spectroscopy analysis, and the spectrum is shown as follows Fig. 9 As shown in FIG. 1 , it is found that the characteristic peaks of the polymer PffBT4T-2OD and SWCNTS appear on the composite film, and a slight red shift occurs, indicating that PffBT4T-2OD and SWCNTS are successfully composited. In addition, the composite thermoelectric film of Example 1 is subjected to X-ray photoelectron spectroscopy surface analysis, and the XPS spectrum is shown in FIG. Fig.10 As shown, according to the peak fitting of the XPS spectrum, it can be seen that in the composite film, the presence of CS bond (286.14eV) can be detected, which is the key evidence for the successful composite of PffBT4T-2OD and SWCNTS, and the presence of π-π bond (290.3eV) can prove that the combination of PffBT4T-2OD and SWCNTS forms a π covalent bond, and this type of valence bond electron activity is high, which is one of the reasons why the composite film has high thermoelectric properties. The peak positions 284.88eV and 285.39eV represent the CC bond of sp3 hybridization and the CC bond of the straight chain, respectively, which come from the six-membered ring in SWCNTS and two CCs formed from different SWCNTS.

[0044] In summary, the film performance test shows that the present invention successfully uses single-walled carbon nanotubes and PffBT4T-2OD for mixed doping to prepare a composite thermoelectric film. Because PffBT4T-2OD is a donor-acceptor type (DA) conjugated polymer, when it is composited with single-walled carbon nanotubes, it provides a strong π-π conjugation effect for the composite, thereby improving the thermoelectric properties of the composite film. In addition, the composite film is low-cost and not easy to damage for inorganic thermoelectric materials. The thermoelectric performance of the films synthesized with different PffBT4T-2OD-SWCNTS ratios was tested using a resistance tester, indicating that the thermoelectric performance of the composite film with PffBT4T-2OD:SWCNTS=2:6 is the best.

[0045] Although embodiments of the present invention have been shown and described, it will be appreciated by those skilled in the art that various changes, modifications, substitutions and variations may be made to the embodiments without departing from the principles and spirit of the present invention, and that the scope of the present invention is defined by the appended claims and their equivalents.

Claims

1. A donor-acceptor type polymer-based flexible thermoelectric film, characterized in that: The flexible thermoelectric film is a composite material formed by mixed doping of single-walled carbon nanotubes and PffBT4T-2OD and has a strong π-π conjugated effect.

2. A method for preparing a thin film as claimed in claim 1, characterized in that: The following steps are included S1, dissolving PffBT4T-2OD and single-walled carbon nanotubes in chloroform and chlorobenzene respectively, and performing ultrasonic oscillation to dissolve them into PffBT4T-2OD solution and single-walled carbon nanotube solution respectively; S2, mixing the PffBT4T-2OD solution and the single-walled carbon nanotube solution, and making them into a mixed solution by stirring and ultrasonic vibration; S3. Filter the mixed solution with suction and filter paper. Remove the solvent during vacuum filtration and retain the mixture on the filter paper. Dry the mixture on the filter paper to form a thin film.

3. The donor-acceptor type polymer-based flexible thermoelectric film according to claim 1, characterized in that: The PffBT4T-2OD is a PffBT4T-2OD having a donor-acceptor type (DA) conjugated polymer, and its structural formula is:

4. The donor-acceptor type polymer-based flexible thermoelectric film according to claim 1, characterized in that: The single-walled carbon nanotubes are ultra-high-purity single-walled carbon nanotubes with a purity of 95%.

5. The method for preparing a donor-acceptor type polymer-based flexible thermoelectric film according to claim 2, characterized in that: In the step S2, the mass ratio of PffBT4T-2OD to single-walled carbon nanotubes in the mixture solution is 2:

6.

6. The method for preparing a donor-acceptor type polymer-based flexible thermoelectric film according to claim 2, characterized in that: The specific operation method of step S3 is: using 0.45 μm microporous filter paper to filter the mixture solution by vacuum filtration, retaining the mixture in the mixture solution on the filter paper and removing the solvent, and then vacuum drying the mixture on the filter paper to obtain a flexible thermoelectric film.